Can proactive rapid response team rounding improve surveillance and reduce unplanned escalations in care? A controlled before and after study. (March 2019) - Danesh, Valerie; Neff, Donna; Jones, Terry L.; Aroian, Karen; Unruh, Lynn; Andrews, Diane; Guerrier, Lotricia; Venus, Sam J.; Jimenez, Edgar
Abstract: Background: Unplanned escalations manifest as a breakdown of hospital care attributable to clinician error through missed or delayed identification of physiological instability, ineffective treatment, or iatrogenic harm. Objectives: To examine the impact of an Early Warning Score-based proactive rapid response team model on the frequency of unplanned intra-hospital escalations in care compared with a rapid response team model based on staff nurse identification of vital sign derangements. Design: Pre- and post Early Warning Score-guided proactive rapid response team model intervention. Setting: 237-bed community hospital in the southeastern United States. Participants: All hospitalized adults (n = 12, 148) during a pre- and post-intervention period. Methods: Logistic regressions used to examine the relationship between unplanned ICU transfers and rapid response team models (rapid response team vs. Early Warning Score-guided proactive rapid response team). Results: Unplanned ICU transfers were 1.4 times more likely to occur during the rapid response team baseline period (OR = 1.392, 95% CI [1.017–1.905]) compared with the Early Warning Score-guided proactive rapid response team intervention period. Conclusions: This study reports a difference in the frequency of unplanned escalations using different rapid response models, with fewer unplanned ICU transfers occurring during the use of Early Warning Score-guided proactive rapid response team model while accounting for differences in admission volumes, age, gender and comorbidities. Implementation of this model has implications for patient outcomes, hospital operations and costs.